A fala e o fato: limites da descentralizacao industrial no Estado de Sao Paulo. - Ronchezel, J. A. (My University, 1983)
Presents some thoughts on the possibility for effective decentralization of industry by the State government of Sao Paulo in terms of the territorial organization of industry and the context of the current (1980) economic and political system.-R.N.Gwynne
(Fact or fiction: limits of industrial decentralization in the state of Sao Paulo, Brazil).